The “refugee crisis” in Europe – between totality and the infinite - Martins, Moisés de Lemos (2019)
The self and the other. Totality and the infinite. In other words, totality as the discourse of the self which erases the other; and the infinite as the discourse of the other, which constrains and imposes reservations on the discourse of totality. I encounter the other in a face-to-face relationship, who thereby starts to exist within me, becomes part of me, constitutes me. This is the path whereby we fall in love, and can also be the path of compassion and solidarity. But the relationship with the other is not exhausted in the encounter. The encounter with the other is often followed by erasure, assimilation, and even domination of the other. Strictly speaking, we can say that the other can never be reduced to the self, i.e. may never be erased within me. And if the issue at stake is to ignore the other, or segregate, discriminate and dominate him, this implies exerting a form of violence over him. This is my starting point and my focus on discussing the “refugee crisis” in Europe.